Oxytocin and Estrogen Receptor β in the Brain: An Overview - Acevedo-Rodriguez, Alexandra; Mani, Shaila K.; Handa, Robert J. (Frontiers in Endocrinology, 2015)
Oxytocin (OT) is a neuropeptide synthesized primarily by neurons of the paraventricular and supraoptic nuclei of the hypothalamus. These neurons have axons that project into the posterior pituitary and release OT into the bloodstream to promote labor and lactation; however, OT neurons also project to other brain areas where it plays a role in numerous brain functions. OT binds to the widely expressed OT receptor (OTR), and, in doing so, it regulates homeostatic processes, social recognition, and fear conditioning. In addition to these functions, OT decreases neuroendocrine stress signaling and anxiety-related and depression-like behaviors. Steroid hormones differentially modulate stress responses and alter OTR expression. In particular, estrogen receptor β activation has been found to both reduce anxiety-related behaviors and increase OT peptide transcription, suggesting a role for OT in this estrogen receptor β-mediated anxiolytic effect. Further research is needed to identify modulators of OT signaling and the pathways utilized and to elucidate molecular mechanisms controlling OT expression to allow better therapeutic manipulations of this system in patient populations.